Analisis Kinerja Terkait Faktor Tunjangan Kinerja, Budaya Organisasi, dan Kecerdasan Emosional (Studi Kasus Pegawai BKPSDM Kabupaten Pidie Jaya) - Fathiah, Alini; Iskandar, Raihan; Luthfi, Luthfi (Singkite Journal, 2025)
Employee performance analysis is the objective of the study. This study is based on performance allowance factors, organizational culture, and emotional intelligence. The research method that will be used is the associative type and quantitative approach. The sample in this study were all employees at the BKPSDM Pidie Jaya Regency, totaling 62 people. The results of the study showed: 1) There is a direct and indirect influence of performance allowances on employee performance of 45.28%, the influence of organizational culture of 35.25%, and the influence of emotional intelligence of 41.39%. 2) Simultaneously, performance allowances, organizational culture and emotional intelligence affect the performance of BKPSDM Pidie Jaya Regency employees with a contribution of 54.1%.